A Historical Analysis of Randomized Controlled Trials in Pediatric Orthopaedic Foot and Ankle Surgery. Issue 1 (January 2022) - Khurshed, Abdulaziz; Abuhantash, Monther; Kay, Jeffrey; Habib, Anthony S.; Kishta, Waleed; de SA, Darren
Category: Ankle; Bunion; Lesser Toes; Midfoot/Forefoot; Trauma Introduction/Purpose: The primary objective of this systematic review was to comprehensively assess the quality of reporting of randomized controlled trials (RCTs) relating to pediatric orthopaedic foot and ankle conditions. Additionally, this current study looked at factors related to the quality of the RCTs and trends in the quality of reporting over time Methods: This systemic review was performed according to an agreed predefined protocol and conducted according to Preferred Reporting Items for Systemic Reviews and Meta-analyses (PRISMA) statement standards. PubMed, Ovid (MEDLINE) and Embase were searched for all RCTs on foot and/or ankle surgery from the database inception until March 31, 2020. The quality of reporting was evaluated using the Detsky quality index and the Consolidated Standards of Reporting Trials (CONSORT) checklist for reporting trials of nonpharmacologic treatments. A multivariate regression analysis was used to assess predictors of quality reporting. Results: The online search yielded 3, 697 articles, 22 of which met the inclusion criteria and were assessed for quality of reporting. The earliest identified RCT was published in 1991. Close to 70% of all RCTs have been produced over the past 10 years (since 2010), and over 90% have been published in the past 20 years (since 2000). There has been a significant increase in the number of RCTs published over time (p=0.042). The mean (SD) Detsky score across all included studies was 69.2% (13.8%). Nine (41%) of the studies were considered 'high-quality' with a standardized Detsky score greater than or equal to 75%. The strongest predictor of quality reporting was the inclusion of a CONSORT flow diagram (β-coefficient: 18.4, p=0.0013). Conclusion: Despite an increase in the quantity of pediatric F&A RCTs over time, the quality has not significantly improved. The use of a CONSORT flow diagram is a strong predictor of high-quality reporting. We encourage investigators to devote more efforts in conducting high-quality RCTs in pediatric orthopaedic foot and ankle, as these are scarce in the literature.